2009
DOI: 10.1111/j.1740-0929.2008.00612.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved conception rates in sows inseminated with cryopreserved boar spermatozoa prepared with a more optimal combination of osmolality and glycerol in the freezing extender

Abstract: Cryoprotectant agents (CPAs) are added in freezing extenders to prevent intracellular ice crystal formation. However, it has been reported that high dose of CPAs confer toxicity on spermatozoa. Recently, the reduction of intracellular water by a high osmolality solution has also resulted in the suppression of ice crystal formation in spermatozoa, suggesting that the optimal combination of glycerol concentration and freezing extender osmolality could contribute to the development of effective sperm cryopreserva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 33 publications
1
28
0
1
Order By: Relevance
“…The conception rate recorded in the present study was in close agreement with that reported by Einarsson et al (1973), but higher than that reported by Graham et al (1971) and lower than that reported by Okazaki et al (2009) in pigs inseminated utilizing frozen semen. The farrowing rate in the present study was comparable with the findings of Didion and Schoenbeck (1996), but higher than that reported by Bathgate et al (2008) and lower than that reported by Didion et al (2011).…”
Section: Resultssupporting
confidence: 92%
“…The conception rate recorded in the present study was in close agreement with that reported by Einarsson et al (1973), but higher than that reported by Graham et al (1971) and lower than that reported by Okazaki et al (2009) in pigs inseminated utilizing frozen semen. The farrowing rate in the present study was comparable with the findings of Didion and Schoenbeck (1996), but higher than that reported by Bathgate et al (2008) and lower than that reported by Didion et al (2011).…”
Section: Resultssupporting
confidence: 92%
“…The results from the second experiment showed that a reduction from the commonly used 3% final glycerol concentration to 0.5–1% resulted in an increased maintenance of post‐thaw motility in both sex‐sorted and non‐sorted sperm frozen at low sperm concentrations. Beneficial effects on the post‐thaw motility of boar spermatozoa frozen in extenders containing a 2% final glycerol concentration, instead of the conventional 3%, have been previously described (Okazaki et al. 2009).…”
Section: Discussionmentioning
confidence: 97%
“…2002). In addition, it has been reported that these damaging effects are related to high glycerol levels (Okazaki et al. 2009) and are ultimately dependent on the number of sperm that are present (Colas 1975).…”
Section: Discussionmentioning
confidence: 99%
“… Seminal plasma is immediately removed by centrifugation after semen collection. The sperm pellet is resuspended in pre‐treatment solution (Modena) that contains both common antibiotics, for example penicillin G and/or amikamycin, and polymyxin B. The resuspended semen is used to make frozen sperm according to Okazaki et al . (2009a).…”
Section: Resultsmentioning
confidence: 99%
“…2008). We also developed a novel freezing extender for pig sperm, which was adjusted for high‐osmotic pressure (400 mOsm/kg) and low‐glycerol concentration (final concentration: 2%) (Okazaki et al . 2009a).…”
Section: Introductionmentioning
confidence: 99%